Struggle on the Axis: The Advance and Retreat of Buddhist Influences in the Political Axis of Capitals in Medieval China (220–907) - Yifeng Xie (MDPI AG, 2021)
Buddhist influences on the sacred axis of the capital during Medieval China (220–907) underwent a process of starting with little impact during the era of Eastern Han, Caowei, and Western Jin (220–317) to a more prominent influence from the late Southern and Northern Dynasties (386–589) to early Tang (618–907), peaked during the reign of Wu Zetian (690–705), and roughly returned to the layout patterns from the late Southern and Northern Dynasties to early Tang after the death of Wu Zetian. As maintained below, the process appears complex in terms of the interaction between Buddhism and political space throughout early Medieval China. There are roughly two modes of integration and interaction between Buddhist buildings and ritual buildings with Buddhist influences and the political axis of the capital: the first mode can be regarded as a typical mode after its establishment in the late Northern Wei Dynasty. This mode exhibits major Buddhist influences, particularly regarding the huge scale of monasteries and pagodas, and the location of high-rise pagodas as landmarks flanking the political axis of the capital. The second mode should be regarded as an atypical mode occurring during the late period of Emperor Wu of the Liang (464–549, r. 502–549), the period of Northern Qi (550–577), and the reign of Wu Zetian. At this point, Buddhist buildings and imperial ritual buildings with Buddhist characteristics and symbolic meanings were placed directly on the political axis of the capital, close to or located at the core of the palace. This practice was a sign that the influence of Buddhism in the political culture and ideology of the entire empire during these eras of Emperor Wu of the Liang, the Northern Qi, and the reign of Wu Zetian had reached their culmination. Architecture reflected the most intuitive embodiment of an external visual form in presenting the most symbolic image of power. With the decline of political enthusiasm for advocating Buddhism, Buddhist and related buildings no longer occupied the political axis of the capital. Various forces majeure such as natural fires, demolition, and reconstruction by subsequent rulers also led to the demise of Buddhist influence on the pollical axis of capital architecture in subsequent eras.